Developing Responsible AI Leadership Capability: A Framework for Governance, Ethics, and AI Literacy - Chilcott, Glenn (Digital Repository of Theses, 2026)
AI has emerged as a general-purpose technology with the capacity to reshape economic activity, organisational structures, and decision-making processes on a global scale. Widely cited economic forecasts suggest that AI could contribute up to $15.7 trillion to global economic output by 2030, positioning it as a central driver of productivity and innovation. However, the acceleration of AI adoption has been accompanied by significant ethical, legal, and societal risks, including algorithmic bias, opacity, data misuse, and the erosion of human agency. These risks challenge existing models of leadership, governance, and accountability. This research identifies a critical leadership readiness gap at the heart of responsible AI adoption. While an overwhelming majority of professionals recognise AI literacy as an essential leadership competency, empirical findings reveal markedly lower confidence in navigating the ethical, regulatory, and governance dimensions of AI in practice. The results expose a persistent disconnect between aspirational commitments to fairness, transparency, and human dignity and the organisational capabilities required to operationalise these principles effectively. Adopting a sequential explanatory mixed-methods research design, this study integrates quantitative survey data with qualitative insights to examine how external regulatory pressures and internal organisational practices shape AI implementation. The findings demonstrate that responsibility for AI governance is frequently fragmented and delegated to technical or compliance functions, rather than embedded within strategic leadership and board-level oversight. This fragmentation contributes to inconsistent decision-making, delayed adoption, and heightened organisational risk. In response, the research introduces the TRAIL (Trustworthy and Responsible AI Leadership) framework, an empirically derived model designed to support leadership capability development for responsible AI. The framework comprises four interdependent pillars: Strategic and Transformational Leadership; Governance and Regulatory Fluency; Ethical and Risk Literacy; and Ethical Data Management. Together, these pillars provide a structured pathway for translating ethical intent and regulatory awareness into practical leadership competence across the AI lifecycle. The study further extends Porter’s Five Forces framework by proposing Responsible AI Capability and Stewardship as a sixth strategic force, arguing that ethical integrity and governance maturity now constitute critical determinants of organisational resilience and sustainable competitive advantage. This reconceptualization positions responsible AI not as a compliance obligation, but as a strategic leadership capability integral to long-term value creation and stakeholder trust. The research concludes that the trajectory of AI adoption will be shaped less by technological sophistication than by the quality of leadership guiding its design, deployment, and use. By advancing an integrative leadership framework grounded in empirical evidence, this study contributes to both theory and practice, offering organisations a practical and human-centred approach to developing AI-literate leaders capable of governing AI responsibly in complex and evolving regulatory environments.